Pengaruh Growth Opportunity, Leverage, dan Ukuran Perusahaan terhadap Konservatisme Akuntansi: (Studi Empiris pada Perusahaan Sektor Properti dan Real estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Marlina Hosianna; Indah Rahayu Lestari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study was conducted to analyze financial distress, leverage, and company size on conservatism. This research was conducted at manufacturing companies in the processed food and beverage sub sectors listed on the Indonesia Stock Exchange for the period 2019-2023. The method of determining the sample in this study using purposive sampling method with a sample of 53 companies in the property and real estate that have met the sample criteria. This study uses multiple linear regression analysis techniques and uses the SPSS version 22.0 statistical test tool. The results of this study show that growth opportunity has no effect, while leverage has a positif and significant effect on accounting conservatism and firm size has a positive and significant effect on acconting conservatism.